Peningkatan Kemampuan Membaca Al-Qur’an Melalui Program Tahsin Bagi Ibu-Ibu Majlis Taklim Di Masjid Iqra’ - Nikmah, Nikmah; Simbolon, Parlindungan; Khasanah, Niswatul; Amirullah, Amirullah; Annajihah, Isra’; Putri, Sabrina (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
The community service program at the Iqra' Tarai Bangun Mosque in Kampar Regency focuses on improving Qur'an reading, with the main objective of improving the Qur'an reading skills of the community around the Iqra' Mosque, especially among mothers. Amidst the current weakness of religious education, especially in Qur'an reading skills, which requires a more innovative, creative, and inclusive approach, this service brings the practice of Tahsin closer to real needs in the field. The methods used include practical methods, questions and answers and discussions, as well as evaluation and feedback with the active involvement of the mothers of the Iqra' Mosque's Islamic study group. The main outcome of this program is an increase in the understanding and skills of mothers in reading the Qur'an. This program has succeeded in showing an increase in the understanding and skills of mothers in the Iqra' Mosque environment in reading the Qur'an. In conclusion, this service program has succeeded in achieving its goal of improving the quality of Qur'an reading by the mothers of the Islamic study group at the Iqra' Mosque by equipping the mothers with the tahsin method. This initiative reflects the importance of reading the Qur'an properly and correctly in everyday life to meet the demands of the times and prepare for the future